Tumor Molecular Features Predict Endometrial Cancer Patients’ Survival After Open or Minimally Invasive Surgeries - Dai, Yibo; Wang, Jingyuan; Zhao, Luyang; Wang, Zhiqi; Wang, Jianliu (Frontiers in Oncology, 2021)
Background: The Cancer Genome Atlas (TCGA) project shed light on the vital role of tumor molecular features in predicting endometrial cancer patients’ prognosis. This study aims to investigate the survival impact of surgical approaches on patients with different genetic alterations. Methods: 473 endometrial cancer patients from TCGA database were selected. To analyze the prognostic impact of surgical approach, survival analyses were conducted in patients with different molecular features. Finally, a simplified molecular stratification model was established to select patients suitable for open or minimally invasive surgery (MIS). Results: In our cohort, 291 patients received open surgery and 182 received MIS. Molecular features influenced patients’ survival after different surgical approaches. Based on survival analyses, 3 molecular subtypes were generated, with subtype 1 harboring POLE mutation (POLEmt), microsatellite-instability high (MSI-H), homologous recombination repair (HRR) pathway mutation or MUC16 mutation (MUC16mt); subtype 3 carrying TP53 mutation; and subtype 2 without specific molecular feature. The survival influence of molecular subtypes depended on surgical approaches. In the open surgery cohort, 3 subtypes showed similar survival outcome, while in the MIS cohort, prognosis varied significantly among 3 subtypes, with subtype 1 the best and subtype 3 the worst. In stepwise Cox regression, molecular subtype was an independent predictor of recurrence-free survival in patients receiving MIS (p<0.001). Conclusion: The molecular features of endometrial cancer are associated with patients’ prognosis after different surgical approaches. MIS should be recommended in patients with POLEmt, MSI-H, HRR pathway mutation or MUC16mt, while for patients with TP53 mutation, open surgery is better concerning oncological safety.